Quality assuring multiple-choice question assessment in higher education - van der Merwe, Hettie (South African Journal of Higher Education, 2016)
A growing scholarship links quality-assured multiple-choice testing to accountable outputs. This article looks at the use of multiple choice assessment and the quality assuring of item development through a structured process of systematic steps. A qualitative investigation was undertaken based on individual e-interviews with participants who are experts in the use of multiple-choice question assessment. The investigation was conducted at the College of Education of a higher education institution. The findings confirm the potential of multiple-choice assessment to test factual knowledge and higher-order learning. The findings also show that the main components in a systematic process of quality assuring the construction of multiple-choice items include training in the skills of item development, peer reviewing of constructed items, professional editing, and the interpretation of statistical analysis of student performance for future constructions. The findings contribute to literature which argues for credible assessment practices to ascertain relevant outputs.